Explicating innovation-based human resource management's influence on employee satisfaction and performance - Lasisi, Taiwo Temitope; Ozturen, Ali; Eluwole, Kayode Kolawole; Avci, Turgay (Emerald Group Publishing Ltd, 2020)
Purpose This study aims to build and test an empirical model that investigates the mechanism with which innovation-based human resource management (HRM) impacts employee satisfaction and performance in Nigerian international airports. Design/methodology/approach A time-lagged approach that involved three-waves was used to collect data from passenger-contact employees and their immediate managers for three-month period starting from January to March 2019. A total of 247 dyads of passenger-contact employees and managers were used for the data analysis. Findings Results from data analysis showed that coworker support and absorptive capacity mediate the impact of innovation-based HRM on employee satisfaction and performance. Innovation-based human resource effort is best applied when coworker support is evident in the workplace. Originality/value The development and application of innovation-driven human resources in the Nigerian aviation context encourage satisfaction with assigned task roles, leading to employee performance. Theory-based implications for managing passenger-contact employees were also given. A significant strength of this study is that it is among the forerunners of scholars that investigated innovation-based HRM as a continuum rather than different aspects of broader management issues.
Keywords: Innovation-based HRM; Employee performance; Employee satisfaction; Absorptive capacity; Nigeria